OVERVIEW OF NUTRITION PROVISION TO CHILDREN UNDER TWO YEARS OLD WITH STUNTING IN NAIBONAT VILLAGE, EAST KUPANG DISTRICT - Gilda Saina,; Ni Ketut Somoyani,; Ni Wayan Suarniti, (Journal of Innovation Research and Knowledge, 2025)
This study was motivated by the number of stunted toddlers in Kupang Regency, especially the Naibonat Health Center. In February 2024 there were 215 toddlers. The number of toddlers under two years old (toddlers) aged 0-24 months in February was 217 toddlers, the number of stunted toddlers in that month was 86 toddlers. The data is supported by several studies showing that stunting is a nutritional problem, especially the provision of additional food nutrition (PMT) for toddlers as an important factor related to stunting. The purpose of this study was to determine the description of the provision of nutrition to stunted toddlers in Naibonat Village, Kupang Regency. The research method is descriptive quantitative with a cross-sectional design. The research was carried out in October-November 2024 using a purposive sampling technique. The sample consisted of 56 mothers. Data collection by distributing questionnaires. Descriptive data analysis. The results of the study showed that the Provision of Nutrition for Toddlers with Stunting in Naibonat Village, East Kupang District, Kupang Regency in 2024 was illustrated in terms of quality and quantity, in the form of: Exclusive breastfeeding with an achievement of 61.4%; Type of PMT achieved 47%; Participation in PMT program assistance health services achieved 50,6%; PMT frequency achieved 67%, and PMT portion achieved 54.5